Characteristics of Obstetric Patients at RSU Cut Meutia North Aceh During the 2020 Covid-19 Pandemic - Iskandar (Britain International for Academic Research (BIAR) Publisher, 2021)
Obstetrics is a medical science that specializes in the study of pregnancy and childbirth. This includes the process before during and after a woman gives birth. The scope of obstetrics includes, antepartum bleeding, postpartum hemorrhage, preterm pregnancy problems, complications in vaginal delivery, pregnancy with gastrointestinal disorders, hypertension in pregnancy, bleeding in the external and internal genitalia, and other diseases. Abortion was the most common disease group in this study, which was 71.4%. Abortion is the termination of pregnancy before the fetus can live outside the uterus at the age of <20 weeks or weight <500 grams. The incidence of abortion is roughly estimated to be 15-20% and 80% occur in the first trimester. This research is a descriptive study with the research design used is a cross-sectional study conducted in the Obstetrics Inpatient Room at the Cut Meutia Hospital, North Aceh. The study was carried out in June 2021 with a population and sample of all patients in the Obstetric Inpatient Room at the Cut Meutia Hospital, North Aceh in 2020. The variables of this study were types of obstetric diseases based on the size group. Univariate analysis was used to describe the characteristics of the types of obstetric diseases that existed in the Obstetric Inpatient Room at the Cut Meutia Hospital North Aceh in 2020. The patients treated in the Obstetric Inpatient Room at the Cut Meutia Hospital North Aceh in 2020 were 244 patients. The percentage of antepartum bleeding was the highest group of diseases in the Obstetrics Inpatient Room at RSU Cut Meutia in 2020, while post-partum bleeding and bleeding in the external and internal genitalia were the least group of diseases. The second most common disease in the Cut Meutia General Hospital in 2020 was hyperemesis gravidarum, then premature rupture of membranes, followed by retained placenta, blighted ovum and preeclampsia.